PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA DI SMKS POOPO - Tiwow, Gilly; Aseng, Livilia F.; Rattu, Febryani (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the effect of learning motivation and learning discipline on student learning outcomes at SMKS Poopo. The tendency to learn less is due to time wasted with mobile phone playing activities and lack of encouragement from family at home and teachers at school to encourage students to learn. This study involved 32 students of grade XI at SMKS Poopo, Variable X1 Learning Motivation, Variable X2 Learning Discipline and Variable Y Learning Outcomes. Partially, the motivation variable influences student learning outcomes, namely based on the t test of 2.126 which is greater than t table with a probability of 0.037. Likewise, learning discipline influences student learning outcomes as seen from the t test of 2.253 which is greater than t table with a probability of 0.027. Although X1 and X2 do not significantly affect Y. shown from the results of the F test obtained Fcount = 2.898. with a probability / significance of 0.061> 0.05 so that Ho is accepted and Ha3 is rejected. Keywords: Learning Motivation, Learning Discipline, Learning Outcomes